Radiological Modelling of Thermaikos Gulf - Eleftheriou, G.; Tsabaris, C.; Monte, L.; Brittain, J. E. (HNPS Advances in Nuclear Physics, 2012)
The radiological model of Thermaikos Gulf ecosystem has been designed based on the MOIRA-PLUS Decision Support System properly modified for the marine environment. Radioactive fallout contamination exercises have been performed for 90Sr and 137Cs radioisotopes, within the frame of environmental sensitivity analysis. The model’s performance has been calibrated, taking into account the available 137Cs deposition estimations and published experimental concentrations to the sediment, the water and the fish at the Gulf, from the time of the Chernobyl accident up to now. The radiation doses to adults – assuming that their entire food intake from the marine pathway comes from the local environment – after the first year of one instantaneous deposition of 1000 Bq/m2, were found 0.72 μSv for 137Cs and 8.8 μSv for 90Sr, respectively. The results are consistent with other models estimations in Northern Seas and NE Aegean Sea.